On a local geometric property of the generalized elastic transmission eigenfunctions and application. (21st September 2021) - Diao, Huaian; Liu, Hongyu; Sun, Baiyi
Abstract: Consider the nonlinear and completely continuous scattering map S ( Ω ; λ, μ, V ), u i = u t ∞ ( x ^ ), x ^ ∈ S n − 1, which sends an inhomogeneous elastic scatterer (Ω; λ, μ, V ) to its far-field pattern u t ∞ due to an incident wave field u i via the Lamé system. Here, ( λ, μ, V ) signifies the medium configuration of an elastic scatterer that is compactly supported in Ω. In this paper, we are concerned with the intrinsic geometric structure of the kernel space of S, which is of fundamental importance to the theory of inverse scattering and invisibility cloaking for elastic waves and has received considerable attention recently. It turns out that the study is contained in analysing the geometric properties of a certain non-selfadjoint and non-elliptic transmission eigenvalue problem. We propose a generalized elastic transmission eigenvalue problem and prove that the transmission eigenfunctions vanish locally around a corner of ∂Ω under generic regularity criteria. The regularity criteria are characterized by the Hölder continuity or a certain Fourier extension property (in terms of the Hergoltz wave approximation) of the transmission eigenfunctions. As an interesting and significant application, we apply the local geometric property to derive several novel unique identifiability results for a longstanding inverse elastic problem by a single far-field measurement.